دور معيار الأهمية النسبية في الحد من مخاطر التحريفات الجوهرية في واقع ممارسات مكاتب التدقيق في الجزائر - ثابت, باديس; العايب, عبد الرحمان (جامعة الوادي - University of Eloued, 2023)
This study aims to know to what extent do the auditors in Algeria are applying the materiality concept in planning and implementing the audit process ; after clarifying the conceptual framework of materiality; the risks of errors and material misstatement. For this purpose we have prepared a questionnaire and distributed it on account keepers and account experts. The study concluded that the auditor faces difficulty in defining the materiality concept and needs guidance to determine it; which enables him to identify the material misstatement and reduce their risks
The role of materiality in reducing the risk of material misstatement in the reality practices of auditing offices in Algeria
مقال
Keywords: الأهمية النسبية ; مخاطر التدقيق ; مخاطر الأخطاء والتحريفات الجوهرية ; تخطيط وتنفيذ عملية التدقيق; Materiality; Audit risks ; Risks of errors and misstatements